C9orf72-Derived Proline:Arginine Poly-Dipeptides Modulate Cytoskeleton and Mechanical Stress Response - Shiota, Tomo; Nagata, Riko; Kikuchi, Sotaro; Nanaura, Hitoki; Matsubayashi, Masaya; Nakanishi, Mari; Kobashigawa, Shinko; Isozumi, Noriyoshi; Kiriyama, Takao; Nagayama, Kazuaki; Sugie, Kazuma; Yamashiro, Yoshito; et al. (Frontiers in Cell and Developmental Biology, 2022)
Proline:arginine (PR) poly-dipeptides from the GGGGCC repeat expansion in C9orf72 have cytotoxicity and bind intermediate filaments (IFs). However, it remains unknown how PR poly-dipeptides affect cytoskeletal organization and focal adhesion (FA) formation. Here, we show that changes to the cytoskeleton and FA by PR poly-dipeptides result in the alteration of cell stiffness and mechanical stress response. PR poly-dipeptides increased the junctions and branches of the IF network and increased cell stiffness. They also changed the distribution of actin filaments and increased the size of FA and intracellular calcium concentration. PR poly-dipeptides or an inhibitor of IF organization prevented cell detachment. Furthermore, PR poly-dipeptides induced upregulation of mechanical stress response factors and led to a maladaptive response to cyclic stretch. These results suggest that the effects of PR poly-dipeptides on mechanical properties and mechanical stress response may serve as a pathogenesis of C9orf72-related neurodegeneration.